The effect of PCM layer on the natural air flow movement in the façade cavity of BiPV system - Čurpek, Jakub; Čekon, Miroslav (EDP Sciences, 2020)
The incorporation of a phase change material (PCM) in building integrated photovoltaic (BiPV) façade can be applied to improve its thermal performance including more effective electrical conversion, however their real interaction needs to be investigated at adequate level. The aim of the presented paper is focused on the application of a material with high latent heat capacity based on PCM in the structure of double-skin BiPV façade. The key aspect concerns on an analysis of natural air flow movement affected by the storing/releasing heat energy from the PCM during daytime/night-time of days. The experimental campaign was performed using an experimental outdoor test cell where two full-scale façade samples (reference BiPV and experimental BiPV/PCM) were investigated. The strong effect of thermal inertia of the PCM identified by experimental measurements was observed on the façade air cavity temperature and air flow movement. Experimental results revealed that natural air flow regimes in façade cavities are nearly equal in the daytime, but in the night-time are totally different. The thermal emission from PCM increase the air temperature in the façade cavity and increase the velocity of air flow movement (PCM started solidified), mainly in the night-time.

The incorporation of a phase change material (PCM) in building integrated photovoltaic (BiPV) façade can be applied to improve its thermal performance including more effective electrical conversion, however their real interaction needs to be investigated at adequate level. The aim of the presented paper is focused on the application of a material with high latent heat capacity based on PCM in the structure of double-skin BiPV façade. The key aspect concerns on an analysis of natural air flow movement affected by the storing/releasing heat energy from the PCM during daytime/night-time of days. The experimental campaign was performed using an experimental outdoor test cell where two full-scale façade samples (reference BiPV and experimental BiPV/PCM) were investigated. The strong effect of thermal inertia of the PCM identified by experimental measurements was observed on the façade air cavity temperature and air flow movement. Experimental results revealed that natural air flow regimes in façade cavities are nearly equal in the daytime, but in the night-time are totally different. The thermal emission from PCM increase the air temperature in the façade cavity and increase the velocity of air flow movement (PCM started solidified), mainly in the night-time.
The effect of PCM layer on the natural air flow movement in the façade cavity of BiPV system
Keywords: BiPV; PCM; ventilated facade; BiPV; PCM; ventilated facade